Adam12 and lnc015192 act as ceRNAs in breast cancer by regulating miR-34a. Issue 49 (6th December 2018) - Huang, Xiaojia; Xie, Xinhua; Liu, Peng; Yang, Lu; Chen, Bo; Song, Cailu; Tang, Hailin; Xie, Xiaoming
Abstract Long non-coding RNAs (lncRNAs) are reported to play vital roles in the progress of multiple cancers. However, the functions of lncRNAs in breast cancer remain to be discovered. We performed microarrays to identify the differentially expressed mRNAs and lncRNAs in breast tissues with or without miR-34a knockout. To explore the functions of the differentially expressed mRNA and lncRNA in breast cancer, we conducted a series of experiments. We found that Adam12 and lnc015192 were significantly upregulated in miR-34a knockout breast tissues. Knockdown of Adam12 and lnc015192 inhibited breast cancer cell migration, invasion, and epithelial–mesenchymal transition (EMT). Further experiments revealed that lnc015192 regulated Adam12 expression by functioning as a competing endogenous RNA (ceRNA) for miR-34a. In summary, our study demonstrate that Adam12 and lnc015192 promote breast cancer metastasis partly by sponging miR-34a through the ceRNA mechanism.